Effect Test of Analgesics (Paracetamol, Ibuprofen, and Antalgin) in Local Strain Male Mice with Acetic Acid Induction Using the Writhing Test Method - Chinthia Devientasaria; Luluk Aniqoh Meliana Putri (Strada Journal of Pharmacy, 2023)
Analgesic or pain blocking drugs are compounds that reduce or eliminate pain without causing loss of consciousness. NSAID (non-steroidal anti-inflammatory drugs) are heterogeneous compounds due to the different chemical structures of NSAID compounds, which are used to reduce mild to moderate pain, such as paracetamol, mefenamic acid, and ibuprofen. Paracetamol is used to reduce body heat caused by infection or something else. In addition, this drug also relieves pain at a mild to moderate level, this analgesic works directly on the body’s heat regulating center in the hypothalamus. The method use is writing test with acetic acid induction. The result of this study indicates that testing the effectiveness of the paracetamol, ibuprofen, and antalgin analgesic drugs in mice study showed that the analgesic power of antalgin was the best compared to paracetamol and ibuprofen.